Análise químico-farmacêutica do ácido fusídico em formulações de creme - Curbete, Mariane Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Fusidic acid is an antimicrobial steroid, indicated in the treatment of serious infections caused by microorganisms of the genus Staphylococcus and other Gram-positive bacteria species, including resistant species to penicillin and other antimicrobials. Research involving the development of more practical analytical methods are relevant to optimize the analysis in the pharmaceutical industry and secure the quality of commercialized product. Thus, this study aimed to develop faster analytical methods, safer for operators, economical and easy to perform, compared to the methods described in the literature for the determination of fusidic acid in the pharmaceutical form of dermatological cream. Fusidic acid was analyzed for its organoleptic and physical-chemical characteristics. Qualitative analysis was performed method by spectrophotometric absorption in the visible region and by thin layer chromatography. For quantification of fusidic acid, were developed and validated two methods: stability indicative method by high performance liquid chromatography, in the concentration range from 5.0 to 95.0 μg mL-1, using mobile phase composed by acetonitrile and water (72:28, v/v), pH 3.5 adjusted with acetic acid and at a wavelength at 210 nm, this method presented average retention time of 8.12 minutes, accuracy of 101.22% and content of 104%; microbiological assay by turbidimetric method, in the concentration range from 0.25 to 2.25 μg mL-1, using casoy broth and 6% of the microorganism Staphylococcus epidermidis ATCC 12228, whose accuracy and mean percentage were 101.95% and 104.60%, respectively. The methods were validated according to ICH guidelines and Brazilian legislation and shown to be accurate, robust, selective, accurate and equivalent to quantify the fusidic acid, at a significance level of 5%. Thus, both methods can be employed in the analysis of fusidic acid in pharmaceutical form of dermatological cream in the pharmaceutical ...

O ácido fusídico é um antimicrobiano esteroide, indicado no tratamento de infecções graves causadas por micro-organismos do gênero Staphylococcus e de outras espécies de bactérias Gram-positivas, incluindo espécies resistentes à penicilina e a outros antimicrobianos. Pesquisas envolvendo o desenvolvimento de métodos analíticos mais práticos são relevantes para otimizar as análises de rotina na indústria farmacêutica e garantir a qualidade do produto comercializado. Desta forma, este trabalho teve como principal objetivo o desenvolvimento de métodos analíticos mais rápidos, seguros para os operadores, econômicos e de fácil execução, em comparação aos métodos descritos na literatura para a determinação do ácido fusídico na forma farmacêutica de creme dermatológico. O ácido fusídico foi analisado quanto às suas características organolépticas e físico-químicas. Também foi realizada análise qualitativa pelo método de espectrofotometria de absorção na região do visível e por cromatografia em camada delgada. Para quantificação do ácido fusídico, foram desenvolvidos e validados dois métodos: método por cromatografia líquida de alta eficiência indicadivo de estabilidade, na faixa de concentração de 5,0 a 95,0 μg/mL, utilizando fase móvel composta por acetonitrila e água (72:28, v/v), pH 3,5 ajustado com ácido acético e comprimento de onda de 210 nm, este método apresentou tempo de retenção médio de 8,12 minutos, exatidão de 101,22% e teor de 104%; ensaio microbiológico pelo método turbidimétrico, na faixa de concentração de 0,25 a 2,25 μg/mL, utilizando caldo casoy e 6% do micro-organismo Staphylococcus epidermidis ATCC 12228, cuja exatidão e percentual médio foram de 101,95% e 104,60%, respectivamente. Os métodos foram validados de acordo com as diretrizes do ICH e da legislação brasileira e mostraram ser precisos, robustos,...
Keywords: Anti-infecciosos; Estafilococos; Controle de qualidade; Fármacos; Quality control